Party Competition and Emotive Rhetoric. (May 2019) - Kosmidis, Spyros; Hobolt, Sara B.; Molloy, Eamonn; Whitefield, Stephen
When do parties use emotive rhetoric to appeal to voters? In this article, we argue that politicians are more likely to employ positive affect (valence) in their rhetoric to appeal to voters when parties are not ideologically distinct and when there is uncertainty about public preferences. To test these propositions, our article uses well-established psycholinguistic affect dictionaries to generate scores from three time series of political text: British party manifestos (1900-2015) and annual party leaders' speeches (1977-2014) as well as U.S. Presidents' State of the Union addresses (1880-2016). Our findings corroborate our expectations and have important implications for the study of party competition by illuminating the role of valence in the way politicians communicate their policies.